CHARACTERISTICS AND RESULTS OF NUTRITIONAL FEEDING CHILDREN IN NATIONAL HOSPITAL OF OBSTETRICS AND GYNECOLOGY IN 2021 (Vietnam Journal of Community Medicine, 2022)
Objective: To evaluate the results of early care and feeding methods for preterm infants at theNeonatal care & treatment Center in the National Hospital of Obstetrics and Gynecology in 2021.Methods: A prospective descriptive cohort study of 189 infants with gestational age from 25 weeksto 32 weeks receiving postpartum care at the Neonatal care & treatment Center in the NationalHospital of Obstetrics and Gynecology from 1/11 2020- 30/6/2021.Results:189 infants received digestible feeding for 1.1 ± 0.3 days and took 16.8 ± 4.8 days to regainbirth weight. The growth velocity of the preterm infants was 14,7 ± 5,9 g/kg/day. 124/189 infants hadPGF (65,61%). The rate necrotizing enterocolitis was 5.8%, only 1 infant died on discharge (0.5%).Conclusion: Feeding premature babies by enteral nutrition is safe, effective, with few complicationsand helps babies to regain to birth weight early.
Keywords: Preterm baby, enteral nutrition, early feeding, postnatal growth failure.